Cranial and endocranial diversity in extant and fossil atelids (Platyrrhini: Atelidae): A geometric morphometric study. Issue 2 (10th April 2019) - Aristide, Leandro; Strauss, André; Halenar‐Price, Lauren B.; Gilissen, Emmanuel; Cruz, Francisco W.; Cartelle, Castor; Rosenberger, Alfred L.; Lopes, Ricardo T.; dos Reis, Sergio F.; Perez, S. Ivan
Abstract: Objectives: Platyrrhines constitute a diverse clade, with the modern Atelidae exhibiting the most variation in cranial and endocast morphology. The processes responsible for this diversification are not well understood. Here, we present a geometric morphometric study describing variation in cranial and endocranial shape of 14 species of Alouatta, Ateles, Brachyteles, and Lagothrix and two extinct taxa, Cartelles and Caipora . Methods: We examined cranial and endocranial shape variation among species using images reconstructed from CT scans and geometric morphometric techniques based on three‐dimensional landmarks and semilandmarks. Principal components analyses were used to explore variation, including the Procrustes shape coordinates, summing the logarithm of the Centroid Size, the common allometric component, and residual shape components. Results: Differences in endocranial shape are related to a relative increase or decrease in the volume of the neocortex region with respect to brainstem and cerebellum regions. The relative position of the brainstem varies from a posterior position in Alouatta to a more ventral position in Ateles . The shape of both the cranium and endocast of Caipora is within the observed variation of Brachyteles. Cartelles occupies the most differentiated position relative to the extant taxa, especially in regards to its endocranial shape. Conclusions: The pattern of variation in the extant species in endocranial shape is similar to the variation observed in previous cranial studies, with Alouatta as an outlier. The similarities between Caipora and Brachyteles were unexpected and intriguing given the frugivorous adaptations inferred from the fossil's dentition. Our study shows the importance of considering both extant and fossil species when studying diversification of complex traits.